(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the essence of STEAM education, its role in shaping the mindset of the new generation, and the harmony between an innovative worldview and spiritual maturity from a philosophical perspective. It demonstrates that under the conditions of accelerating digital transformation, the STEAM approach not only develops technical and scientific competencies but also fosters qualities such as creativity, critical thinking, and moral responsibility. The article highlights the integrative and comprehensive nature of STEAM education in forming the cognitive culture, cognitive flexibility, and spiritual maturity of the new generation.